Determinants of elite disability sport performance - Martin, J. J. (Kinesiology Review, 2015)
In the last 10-20 years sport psychologists have started to emphasize the value of mental strengths such as self-confidence for disability sport athletes (Martin, 2012). The pinnacle of disability sport competition, the Paralympics, is becoming increasingly competitive, suggesting a strong need for athletes to possess effective mental skills. Like the Olympics there is intense pressure to win at the Paralympics. In the current review article I discuss the body of knowledge in sport psychology that focuses on potential direct and indirect determinants of performance in elite disability sport. The review is organized around a personnel developmental model used by Martin (1999, 2005, 2012). This model is a humanistic model and revolves around foundation qualities, psychological methods and skills, and facilitative and debilitative factors. The premise of the model is also similar to McCann`s sentiment that "at the Olympics [Paralympics], everything is a performance issue" (2008, p. 267). http://www.nationalacademyofkinesiology.org/speaker-videos/2014-speaker-videos/determinants-of-elite-disability-sport-performance